The tasks of care: between love, self-denial and inequity ... what is not see. - Krynveniuk, Marta; Rua, Gabriela Veloz; Cuman, Graciela; Antonelli Marcelino Brabo, Tânia Suely (Faculdade de Filosofia e Ciências, 2022)
With the pandemic and quarantine situation, care took on a visibility and relevance in daily life and in the government agenda of our country never before considered necessary. It has become evident how the social organization of care is unfair specifically for women, thus accountingfor their unequal distribution, reproducing inequalities and making their value invisible.From a reflective analysis of our own experience as sexual, historical people, with desires and affections, with knowledge situated according to the teachings of feminisms, we carry out this communication focusing on domestic and care work that show a triple inequality:they are carried out by women, the majority after the working day, which is usually less paid than that of men and without any remuneration: in addition, due to overload, it impacts our health. Even today, in all cultures, the private sphere is the space of imbalances and injustices from the sexual division of labor and cultural stereotypes, being one of the first inequalities between human beings: the field of care appears as the most important, hard and invisible nucleus of gender inequality. Based on what has been analyzed, we consider the urgent need to review and rethink family roles to promote co-responsibility and reciprocity of care, challenging masculinities, trying to overcome heteropatriarchal norms to denature and de-feminize them.